The Impact of Internet Banking Service Quality on Customer Satisfaction: The Role of Information Technology in Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
With the integration of markets and increasing trends of globalization world over, no any nation whether big or small, developed or developing, can ignore what is happening around. India being of the most promising emerging markets, cannot ignore these globalization trends. India has definitely an edge over its competitors in the area of Information Technology (IT). Information technology has given a new shape to the financial sector in general and banking industry in particular and the most beneficial sectors due to the adoption of IT enables services. The technology plays a major role in the efficiency of operations and also provides the competitive edge for the success of banks. As far as India banking industry is concerned, it can be said that although the Indian banks may not be as technologically advanced as their counterparts in the developing countries, they are following the same standards as the overseas banks in the IT front.